ISLAMIC FINANCIAL LITERACY DAN ISLAMIC FINANCIAL BEHAVIOUR MAHASISWA (Studi Etnometodologi Terhadap Efektivitas Pembelajaran Manajemen Keuangan Islam) - Muhammad Fakhri Amir (UIN Mataram, 2021)
This study aims to determine whether the learning process of Islamic Financial Management courses has been effective in improving students’ Islamic financial literacy and Islamic financial behaviour. This study is a qualitative research, using an ethnomethodological approach, to be more specific this study employs an Islamic ethnomethodology analysis tool, namely